German and the rest of euro area fiscal policy during the crisis - Niklas Gadatsch; Klemens Hauzenberger; Nikolai Stähler (Deutsche Bundesbank, 2015)
We present the estimated large-scale three-region DSGE model GEAR picturing Germany, the Euro Area and the Rest of the world. Compared to existing models of this type, GEAR incorporates a comprehensive fiscal block, involuntary unemployment and a complex international structure. We use the model to evaluate spillovers of fiscal policy, to calculate various present-value multipliers for distinct fiscal instruments, and to assess how discretionary fiscal policy in Germany and the Euro Area affected GDP growth during the global financial crisis. Our analysis suggests that spillovers of fiscal policy shocks in the Euro Area are small. Overall, spending multipliers are higher than revenue-based multipliers and are in line with those found in the literature. We find that, during the crisis, fiscal stimulus packages increased annualized quarter-on-quarter GDP growth substantially, both in Germany and in the rest of the Euro Area. The main drivers of GDP growth in Europe, however, were rest of the world and uncovered interest rate parity shocks, followed by domestic non-fiscal shocks.
Keywords: H2; J6; E32; E62; 330; Fiscal Policy; Unemployment; DSGE modeling; Bayesian estimation